PENGARUH PEMBERIAN EKSTRAK ETANOL RUMPUT LAUT MERAH (Gracilaria verrucosa) TERHADAP WAKTU PENDARAHAN (BLEEDING TIME) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Keni Idacahyati; Dimas Rahman Fauzi; Tresna Lestari (Jurnal Insan Farmasi Indonesia, 2020)
Antiplatelet is a drug used to prevent excessive formation of b platelets in cardiovascular disease. The use of antiplatelet can cause resistance and side effects and cause death. Red seaweed (Gracilaria verrucosa) contains flavonoids which are polyphenol compounds which have activity can inhibiti platelet aggregation because of their ability to inhibit arachidonic acid released from membrane phospholipids through rapid coordinated activation of phospholipases from cell membranes so that the metabolic pathway of cyclooxygenase becomes inhibited. This study aims to determine the effect of ethanol extract of red seaweed on bleeding time. This method using is experimental study of 5 groups, each group consisted of 5 rats there were group of positif control, negative control, seaweed extract doses ( 300,600,1200)mg/BW with a bleeding time parameter. The results showed that the administration of 600 mg / kg BW Rats could extend the bleeding time in proportion to positive control.